2011
DOI: 10.1007/s10646-011-0630-4
|View full text |Cite
|
Sign up to set email alerts
|

Low exposure levels of urban metals induce heterotrophic community tolerance: a microcosm validation

Abstract: The biological response of periphyton chronically exposed to metals of urban origin (Cd, Ni and Zn) was investigated with a Pollution-Induced Community Tolerance (PICT) approach using a previously developed short-term toxicity test based on β-glucosidase (heterotrophic) activity. Periphyton was grown on plastic membranes immersed in indoor aquaria contaminated with metals at realistic contamination levels (0.3, 3 μg/l for Cd, 5, 50 μg/l for Ni, 20, 200 μg/l for Zn). After 3 weeks of exposure, biofilms' paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 33 publications
3
28
1
1
Order By: Relevance
“…A 319 maximum % inhibition inferior to 100% means that -glucosidase activity cannot be fully 320 inhibited by short-term exposure to metals even at high exposure concentrations (the highest 321 metal concentrations tested are 10 mM namely 2.07 g/L for Pb). This phenomenon was already 322 observed in previous studies on laboratory or in situ exposed biofilms with the same toxicity test 323 (Fechner et al, 2011;Fechner et al, 2012a). In the present study, -glucosidase toxicity tests 324 revealed the impact of Pb exposure on the Pb 100 biofilm with a 1.7 increase of normalized EC 50 325 value and a significant decrease of maximum % inhibition (72.30 %) when compared to Pb 0 326 (Figure 2 and Table 5).…”
Section: Pb Exposure Concentrations (Left Graphs) 287supporting
confidence: 83%
See 4 more Smart Citations
“…A 319 maximum % inhibition inferior to 100% means that -glucosidase activity cannot be fully 320 inhibited by short-term exposure to metals even at high exposure concentrations (the highest 321 metal concentrations tested are 10 mM namely 2.07 g/L for Pb). This phenomenon was already 322 observed in previous studies on laboratory or in situ exposed biofilms with the same toxicity test 323 (Fechner et al, 2011;Fechner et al, 2012a). In the present study, -glucosidase toxicity tests 324 revealed the impact of Pb exposure on the Pb 100 biofilm with a 1.7 increase of normalized EC 50 325 value and a significant decrease of maximum % inhibition (72.30 %) when compared to Pb 0 326 (Figure 2 and Table 5).…”
Section: Pb Exposure Concentrations (Left Graphs) 287supporting
confidence: 83%
“…DW and AFDW also decreased for the Pb 100 biofilm but 314 increased slightly for Pb 1 and Pb 10 communities. A similar effect was observed on DW for 315 biofilms exposed to low metal concentrations (Morin et al, 2008;Fechner et al, 2011). 316…”
Section: Pb Exposure Concentrations (Left Graphs) 287supporting
confidence: 56%
See 3 more Smart Citations